The analysis of thermal behavior in ferromagnetic core using boundary element method - (:unkn) unknown (My University, 2008)
This study presents a method for computing thermal properties of an actuator and compares various magnetic materials. The two-dimensional heat conduction problem is studied using the boundary element method (BEM) with Poisson equivalence. Linear elements are used in the solution procedure. The temperature distribution in the ferromagnetic body is evaluated under stationary condition. The numerical results have been compared with the results of the finite element method (FEM). Numerical experiments have been carried out on soft ferromagnetic materials such as silicon steel iron; mild iron; pure iron and amorf and results the temperature distribution are graphed.
Keywords: Actuator; Boundary element method; Ferromagnetic materials; Finite element method; Thermal analysis